Commonly observed shortcomings in manuscripts submitted to management journals - Naresh Khatri; Arup Varma; Pawan Budhwar (IIMB Management Review, 2017)
We outline commonly noticed shortcomings and ways to overcome them in the manuscripts submitted by new management researchers, such as doctoral students and junior faculty. The usual pitfalls in manuscripts submitted to business and management journals include poor writing and presentation, lack of integration, lack of significance, poor research design, and scanty description of methods, untidy presentation of results, and inadequate and sloppy discussion and implication sections. Borrowing from our experiences and the writings of the editors of top tier management journals, we offer guidelines for crafting clear and persuasive manuscripts. We provide suggestions for developing each section of the manuscript: topic choice, abstract, introduction, theory and grounding of hypotheses, research design, methods and results, discussion and implications, and references.